A Noninvasive Imaging Toolbox Indicates Limited Therapeutic Potential of Conditionally Activated Macrophages in a Mouse Model of Multiple Organ Dysfunction - Jack Sharkey; Lorenzo Ressel; Nathalie Brillant; Lauren Scarfe; Bettina Wilm; B. Kevin Park; Patricia Murray (Stem Cells International)
Cell-based regenerative medicine therapies require robust preclinical safety, efficacy, biodistribution, and engraftment data prior to clinical testing. To address these challenges, we have developed an imaging toolbox comprising multispectral optoacoustic tomography and ultrasonography, which allows the degree of kidney, liver, and cardiac injury and the extent of functional recovery to be assessed noninvasively in a mouse model of multiorgan dysfunction. This toolbox allowed us to determine the therapeutic effects of adoptively transferred macrophages. Using bioluminescence imaging, we could then investigate the association between amelioration and biodistribution. Macrophage therapy provided limited improvement of kidney and liver function, although not significantly so, without amelioration of histological damage. No improvement in cardiac function was observed. Biodistribution analysis showed that macrophages homed and persisted in the injured kidneys and liver but did not populate the heart. Our data suggest that the limited improvement observed in kidney and liver function could be mediated by M2 macrophages. More importantly, we demonstrate here the utility of the imaging toolbox for assessing the efficacy of potential regenerative medicine therapies in multiple organs.